2022
DOI: 10.3389/fsufs.2022.900230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cotton–Peanut Intercropping Patterns on Cotton Yield Formation and Economic Benefits

Abstract: Intercropping has been widely adopted by farmers because it often enhances crop productivity and economic returns. However, to increase the comprehensive production benefits of agricultural cultivation and increase the economic benefits of cotton in Northwest Shandong Province, a set of green, ecological, and efficient intercropping mode suitable for Northwest Shandong Province was preliminarily formed. A 2-year intercropping experiment was conducted in Xiajin and Dongping counties in Shandong Province, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The results of a 2022 study (Wang et al 2022) conducted on the economic evaluation of intercropping of cotton with peanuts showed that intercropping reduced costs and increased resource use efficiency and finally increased the farm's net income. The authors stated that the intercropping system could not only increase the crop yield per unit area but also provide notable economic benefits, which increase farmers' tendency to favor implementing intercropping rather than sole cropping in cotton cultivation (Wang et al 2022).…”
Section: Monetary Advantage Index (Mai)mentioning
confidence: 99%
“…The results of a 2022 study (Wang et al 2022) conducted on the economic evaluation of intercropping of cotton with peanuts showed that intercropping reduced costs and increased resource use efficiency and finally increased the farm's net income. The authors stated that the intercropping system could not only increase the crop yield per unit area but also provide notable economic benefits, which increase farmers' tendency to favor implementing intercropping rather than sole cropping in cotton cultivation (Wang et al 2022).…”
Section: Monetary Advantage Index (Mai)mentioning
confidence: 99%